2022
DOI: 10.1021/acsami.2c12164
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Functionalized Microporous MOFs for Capturing Greenhouse Gases CF4 and NF3 with Record Selectivity

Abstract: The capture and separation of fluorinated gases (F-gases) from N2 has the potential to not only reduce greenhouse gas emissions but also provide economic benefits for the semiconductor industry. In this work, two Ni-based metal–organic frameworks (MOFs), Ni-MOF (Ni­(ina)2, ina = isonicotinic acid) and amine-functionalized NH 2 –Ni-MOF (Ni­(3-ain)2, 3-ain = 3-aminoisonicotinic acid), were constructed for capturing F-gases (CF4 and NF3). At ambient conditions, both materials exhibit very high CF4 sorption capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Yang and co-workers reported the Ni-MOF and NH 2 -Ni-MOF in gas-phase adsorption ground selective adsorption performance. It was found that the pore size of NH 2 -Ni-MOF was smaller than that of Ni-MOF due to the modified −NH 2 , indicating that amino-functionalized groups significantly affect CF 4 /N 2 selectivity . In addition, differences in the adsorption behavior of pristine and NH 2 -functionalized MOFs on toxic dye molecules have also been investigated in previous reports.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Yang and co-workers reported the Ni-MOF and NH 2 -Ni-MOF in gas-phase adsorption ground selective adsorption performance. It was found that the pore size of NH 2 -Ni-MOF was smaller than that of Ni-MOF due to the modified −NH 2 , indicating that amino-functionalized groups significantly affect CF 4 /N 2 selectivity . In addition, differences in the adsorption behavior of pristine and NH 2 -functionalized MOFs on toxic dye molecules have also been investigated in previous reports.…”
Section: Introductionmentioning
confidence: 95%
“…37 NH 2 -Ni-MOF was smaller than that of Ni-MOF due to the modified −NH 2 , indicating that amino-functionalized groups significantly affect CF 4 /N 2 selectivity. 38 In addition, differences in the adsorption behavior of pristine and NH 2 -functionalized MOFs on toxic dye molecules have also been investigated in previous reports. It was reported that NH 2 -MIL-53(Al) has a higher adsorption capacity than MIL-53(Al) due to the hydrogen bonding interaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Porous coordination polymers (PCPs), also named metal‐organic frameworks (MOFs), show a large specific surface area, abundant and adjustable pore size, and diverse structures, which make them widely studied in many fields, especially for gas adsorption and separation. [ 14‐22 ] Various CO 2 capture and separation methods based on MOFs have been reported. [ 6,23‐25 ] It is imperative to consider issues such as high‐pressure drops, pipe clogging, and dust contamination when using MOFs in the large‐scale chemistry industry.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Therefore, systematic studies on the CF 4 /NF 3 mixture separation performance of various MOFs by computational chemistry is an efficient and promising way to solve the existing CF 4 /NF 3 separation issues. Wang et al successfully synthesized Ni-MOFs and NH 2 -Ni-MOFs by experiments and highlighted that −NH 2 -functionalized MOF exhibits excellent adsorption performance for CF 4 and NF 3 , indicating that MOF materials possess great potential in separating CF 4 and NF 3 . The separation of CF 4 /NF 3 by physical adsorption using MOFs as an adsorbent is beneficial to the adsorbent regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, systematic studies on the CF 4 /NF 3 mixture separation performance of various MOFs by computational chemistry is an efficient and promising way to solve the existing CF 4 /NF 3 separation issues. Wang et al 24 The separation of CF 4 /NF 3 by physical adsorption using MOFs as an adsorbent is beneficial to the adsorbent regeneration. Moreover, the advantages of flexible processing capacity, simple equipment, no byproducts, and high automation make it widely used in the field of gas separation.…”
Section: Introductionmentioning
confidence: 99%